Alih Kode Pada Konten Vlog Dalam Kanal Youtube Turah Parthayana - Istikharoh Istikharoh; Alifiah Nurachmana; Linggua Sanjaya Usop; Paul Diman; Syarah Veniaty (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2023)
The aims of the research are (1) to describe the forms of code switching contained in the content YouTube Turah Parthayana, (2) describes the form of code switching contained in the contentYouTube Turah Parthayana, (3) describes the factors that cause code switching in the contentYouTube To install Turah Parthayana. This research is a qualitative descriptive study. This research with sociolinguistic studies focuses on aspects of code switching. The data sources in this study are three video content shows owned by Turah Parthayana. The data collection technique in this study used the free-involved viewing method. Based on the results of the analysis, it can be concluded that the three video views are contentYouTube From that, the code switching data found was 44 data. The forms of temporary code switching and permanent code switching were both found by the researcher, namely 5 data. Forms of code switching found at the phrase level found 16 data, 10 data clause levels, 5 sentence levels, and 3 data inter-sentence levels. The factors that cause code-switching found are factors of talking about a certain topic, quoting other people, inserting interjections (expressive words of feeling, doing repetition used for clarification and intention to clarify the speaker's content to the other person